Effectiveness of Integrating Skimming, Scanning, and Close Reading in Arabic Instruction - Rahmat Hidayat; Ulfa Muna Kamila; Agus Yasin; Abdul Hafidz Bin Zaid (Al-Lahjah : Jurnal Pendidikan, Bahasa Arab, dan Kajian Linguistik Arab, 2026)
ABSTRACT Reading (mahārat al-qirā’ah) is the linguistic skill through which learners of Arabic as a foreign language gain the widest access to knowledge, yet it remains one of the most difficult competencies to develop because it demands the simultaneous coordination of decoding, vocabulary knowledge, and higher-order comprehension. This study examines the effectiveness of integrating three complementary reading strategies skimming, scanning, and close reading within Arabic reading instruction. Using a systematic literature review guided by the PRISMA protocol, the study synthesised twenty-two peer-reviewed articles published between 2021 and 2026 in reputable indexed journals addressing reading-strategy instruction in second- and foreign-language settings, with particular attention to Arabic. The findings indicate that skimming and scanning reliably improve reading speed and the efficient location of information, that close reading deepens inferential and critical comprehension, and that the greatest gains occur when the three strategies are taught as a sequenced, integrated repertoire rather than in isolation. In Arabic instruction specifically, integration helps learners manage the language’s morphological density, unvowelled script, and register variation, while vocabulary knowledge and metacognitive awareness function as decisive mediating factors. The review concludes that an explicitly modelled, gradually released three-strategy sequence offers a coherent pedagogical framework for Arabic reading instruction and identifies the need for controlled experimental studies within Arabic classrooms to strengthen the evidence base.